Performance investigation of PA6/HIPS blends compatibilized with SEBS-MA. Effect of compatibilizer content on mechanical, thermomechanical, torque rheometry and morphology properties (Research, Society and Development, 2021)
Blends of polyamide 6 (PA6) with high-impact polystyrene (HIPS) were prepared, using maleic anhydride grafted styrene-(ethylene-butylene)-styrene copolymer (SEBS-MA), as a compatibilizer agent. The blends were prepared in a co-rotating twin-screw extruder and subsequently injection molded. The properties of torque rheometry, Izod impact strength, heat deflection temperature (HDT) and scanning electron microscopy (SEM) were investigated. The results showed that there was an increase in the torque of the PA6/HIPS blends with the addition of the SEBS-MA compatibilizer. Impact strength and HDT increased by 56% and 24.5 % compared to neat PA6 when the PA6/HIPS blended formulation contains 15 pcr of SEBS-MA. This blend showed greater stability in morphology, as verified in the SEM, with better interfacial adhesion and less voids, resulting mainly in greater impact strength. In general, the impact strength and HDT properties of PA6 can be adapted and improved by developing polymer blends.